Projeto experimental de Publicidade e Propaganda: Projeto Goles de Afeto - Foschiera, Carolina Bugança (2019)
The Goles of Afeto project was born in 2015 as an initiative of the journalist Victória Holzbach. Its main objective is to promote kind actions that affect those who receive them, transforming their days in a positive way. This experimental project's main objective is to transform Goles de Afeto into a promoter of a kind of “Kindness Network”, inspiring those who were impacted by a setback with another gesture of affection in society. The realization of this work divided into six stages: getting to know the organization of Goles de Afeto, creating a life-long experience, getting to know people who disseminate kindness, planning a campaign through the solidification of communication strategies and creating and producing campaign communication . Even if in an intangible way, we perceive the effectiveness of the actions considered in this work due to the adherence and positive vision of the community for the work carried out by the agents of kindness.